Development and validation of a UPLC-MS method for determination of atazanavir sulfate by the “analytical quality by design” approach - Saha Chandni; Gupta N. Vishal; Chandan R. S. (Acta Pharmaceutica)
A UPLC-MS method for the estimation of atazanavir sulfate was developed using the “analytical quality by design” approach. The critical chromatographic quality attributes identified were retention time, theoretical plates and peak tailing. The critical method parameters established were percent of organic modifier, flow rate and injection volume. Optimization performed using Box-Behnken Design (BBD) established 10 % organic modifier, 0.4 mL min−1 flow rate and 6-µL injection volume as the optimum method conditions. Atazanavir sulfate eluted at 5.19 min without any interference. Method validation followed international guidelines. The method has proven linearity in the range of 10–90 µg mL−1. Recovery was between 100.2–101.0 % and precision within the accepted limits (RSD 0.2–0.7 %). LOD and LOQ were 2.68 and 8.14 µg mL−1, resp. Stress testing stability studies showed atazanavir sulfate to degrade under acidic and basic conditions. The suggested technique is simple, rapid and sustainable. It is, therefore, suggested for routine analysis of atazanavir sulfate.